Traditional Alliances and Intergroup Relaltions of Bakor Groups in the Middle Cross River Region, Nigeria 1600-1900 - Frank N Enor; Etu Gboshe; Fidelis Ngaji Akwaji (Social Sciences, Humanities and Education Journal (SHE Journal), 2023)
The Bakor speaking group in the middle Cross River Region is a group of north and north-western Ejagham people who share a contiguous homeland from Nde in Ikom Local Government Area to Ogoja Local Government Area in the upper Cross River Region. Their history, culture, and geographical spread provide a homogeneity unparallel in the region; yet, the Bakor evolved a delicate system of alliances dedicated to warfare as a modus vivendi at a period when land became highly contestable following pressure from new arrivals from the north-east and west of their homeland. This paper has attempted to trace the historical trajectory of some Bakor groups from their formative stages to the 20th century. The basis for their alliances, the factors of contacts and relations with neighbors far and near, and their socio-political elaborations as the fulcrum of their unity have all been examined. The historical-analytical method has been adopted to examine data derived from primary investigation of the region spanning three summer holidays. Findings, inter alia, have shown that, with some exceptions, warfare does not constitute deep discontinuities in the intergroup relationships of traditional societies. Among this study group, traditional alliances, warfare, and other socio-cultural factors provided the basis for the formation of ethnic identity and unity among the Bakor people